1997
DOI: 10.1074/jbc.272.8.5105
|View full text |Cite
|
Sign up to set email alerts
|

Model Peptide Studies Demonstrate That Amphipathic Secondary Structures Can Be Recognized by the Chaperonin GroEL (cpn60)

Abstract: The molecular chaperone cpn60 binds many unfolded proteins and facilitates their proper folding. Synthetic peptides have been used to probe the question of how cpn60 might recognize such a diverse set of unfolded proteins. Three hybrid peptides were synthesized encompassing portions of the bee venom peptide, apamin, and the sequence KWLAESVRAGK from an amphipathic helix in the NH 2 -terminal region of bovine rhodanese. Two disulfides connecting cysteine residues hold the peptides in stable helical conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The same conclusion can be drawn from the studies using ␣-casein as a substrate protein and crystal structure of minichaperone in which a peptide with a roughly extended conformation occupied the polypeptide binding site of GroEL (17). It should be added, however, that this does not exclude the possibility that some peptides that interact weakly with GroEL adopt a conformation of ␣-helix when binding to GroEL (37)(38)(39)(40). It is our current view that the polypeptide binding site of GroEL may be flexible enough to accept an ␣-helix form of peptides that expose hydrophobic residues but that an extended form of peptides with hydrophobic residues should be a more favorite substrate.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The same conclusion can be drawn from the studies using ␣-casein as a substrate protein and crystal structure of minichaperone in which a peptide with a roughly extended conformation occupied the polypeptide binding site of GroEL (17). It should be added, however, that this does not exclude the possibility that some peptides that interact weakly with GroEL adopt a conformation of ␣-helix when binding to GroEL (37)(38)(39)(40). It is our current view that the polypeptide binding site of GroEL may be flexible enough to accept an ␣-helix form of peptides that expose hydrophobic residues but that an extended form of peptides with hydrophobic residues should be a more favorite substrate.…”
Section: Resultsmentioning
confidence: 63%
“…Studies using a variety of proteins as a model of substrate protein have been carried out, but they have led to several different proposals on the GroELrecognizable structural features, ranging from a fully unfolded to native-like conformation (28 -36). Some proteins (short peptides) containing ␣-helices were reported to bind to GroEL (37)(38)(39)(40), although it was shown that an all or mainly ␤-sheet protein (Fab fragment, pepsin, and green fluorescent protein) could bind to GroEL (16,41,42). On the other hand, binding of GroEL to unfolded proteins without an ordered secondary structure, apocytochrome c (33) and ␣-casein (21), was demonstrated.…”
mentioning
confidence: 99%
“…These regions were highly populated with hydrophobic amino acids, forming both hydrophobic and amphipathic -helices in the native state. More recent studies with small model peptides also support a key role for large stretches of hydrophobic surface in substrate protein recognition by GroEL (Brazil et al, 1997;Chen and Sigler, 1999;Preuss et al, 1999;. Complementary observations on the role of hydrophobic interactions have also been made with GroEL itself.…”
Section: Recognition Of Substrate Proteins By Groelmentioning
confidence: 68%
“…These data confirm that the chaperone sites represent hydrophobic site(s). The observation of bis-ANS binding to a 19-amino acid linear peptide was surprising, because binding of bis-ANS or other fluorescent probes to only synthetic cyclical peptides has been reported earlier (33,34).…”
Section: Interaction Of Bis-ans Withmentioning
confidence: 99%